Advances in Quantum properties of Graphene applied for targeted functional Nanomaterials and Metamaterials - Bracamonte, Angel Guillermo (2023)
In the present work we describe the most important quantum properties of graphene and derivatives recently published. We discuss how these properties were incorporated into varied hybrid materials such as substrates for specific tuning of matter to track varied quantum signals. Their potential applications were analyzed from nanomaterial and nanotechnology. In particular graphene, its derivatives and other carbon-based allotropes were chosen due to their special chemical structure and properties from the nanoscale to larger lengths, according to specific applications. As expected, these carbon-based and related materials’ highly ordered and condensed electronic configuration showed particular electronic properties below the nanoscale. Thus, we discussed the generation of pseudo-electromagnetic fields and conduction bands. This particular property could also interact with different quantized energy levels and quantum properties, such as those focused on: i) Dirac electron interaction and conduction, ii) anomalous quantized hall effects, iii) magnetic effects, iv) excitons, v) polaron generations, d vi) Fermi and Landau levels. These different phenomena were discussed about the particular topological states of graphene by tuning their 3D chemical structures. Therefore, quantum phenomena and their possible modifications such as quantum interference, potential improvements and encrypted signal transduction were considered for applications.